Tracing the Digital Footprints: Blockchain Analysis and Cryptocurrency Crime Investigation - Gargi Pachuri (AG Volumes, 2026)
Blockchain technology and cryptocurrencies have transformed the world of digital financial systems, providing decentralized, transparent, and secure digital transactions. Their widespread adoption has also made them easier to use for cybercrime activities like ransomware, money laundering, phishing, operating a darknet marketplace, investing and even terrorist financing. This review explores how blockchain analytics can be used to trace digital footprints, aiding cryptocurrency crime investigations. It covers the basics of the blockchain architecture, transactional operations of cryptocurrencies, as well as relevant forensics methods such as transaction graph analysis, wallet clustering, address attribution, and fund tracing. The review also describes some of the most common crimes involving cryptocurrencies, typical digital investigation processes, and the use of blockchain forensic tools. Finally, it has identified the technical hurdles associated with technologies that enhance privacy, legal and regulatory concerns in India, and trends like artificial intelligence-based blockchain analytics and cross-chain forensic investigations to improve the detection and digital forensic capabilities of cybercrime in the future.